Dopaminergic Neurotransmission in Patients with Schizophrenia in Relation to Positive and Negative Symptoms - Pogarell, O.; Koch, W.; Karch, S.; Dehning, S.; Müller, N.; Tatsch, K.; Poepperl, G.; Möller, H.-J. (Pharmacopsychiatry, 2012)
Schizophrenia is a complex dynamic disorder comprising a wide range of neurobiological alterations including dopaminergic dysfunction. The aim of the study was to investigate dynamic changes of dopaminergic neurotransmission in patients with schizophrenia (n=8, mean age 25.4±5.8 years) in early stages of the disorder, compared to healthy control subjects (n=7, mean age 23.6±2.7 years). A dynamic IBZM SPECT protocol was used to assess the endogenous dopamine release following an amphetamine challenge. Subjects received a bolus activity of 175 MBq followed by a continuous infusion of 45 MBq/h [123I]IBZM. SPECT scans were performed 2 h after bolus injection, and 1 h following the amphetamine challenge (0.3 mg/kg). Striatal IBZM binding to dopamine D2 receptors was assessed with a volume-of-interest (VOI) technique. The change in IBZM binding between pre- and post-challenge scans was used as a measure of endogenous dopamine release triggered by amphetamine. At baseline, patients showed higher mean striatal IBZM binding compared to controls (0.77±0.09 vs. 0.68±0.07, p=0.07). There was a statistically significant difference in IBZM binding between patients, with a predominance of negative vs. positive symptoms (0.84±0.08 vs. 0.71±0.04, p<0.05). Upon amphetamine challenge, mean IBZM binding decreased by about 4.9±7.6% in controls (n=7) compared to a mean of 12.4±5.8% in subjects with schizophrenia (p<0.05). In patients, paranoid symptoms showed a significant negative correlation with IBZM baseline binding, whereas there was a trend towards positive correlation with the decrease of IBZM binding under challenge. Negative symptoms showed positive associations with baseline IBZM binding. The data are in line with previous reports and contribute to the notion of a dynamic instability of the dopaminergic system in patients with schizophrenia, taking into account the psychopathology with respect to positive or negative symptoms.
Keywords: schizophrenia; dynamic systems disorder; dopamine; IBZM SPECT; amphetamine challenge